Ecosystem approaches to human health Abordagens ecossistêmicas à saúde humana - N. Ole Nielsen (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2001)
The promotion of human health must be embedded in the wider pursuit of ecosystem health. Interventions will be impaired if ecosystem-linked determinants of health are not taken into account. In the extreme case, if ecosystems lose their capacity for renewal, society will lose life support services. Essential features of ecosystem health are the capacity to maintain integrity and to achieve reasonable and sustainable human goals. An ecosystem approach to research and management must be transdisciplinary and assure participation of stakeholders. These requisites provide a means for science to better deal with the complexity of ecosystems, and for policy-makers and managers to establish and achieve reasonable societal goals. The ecosystem approach can determine links between human health and activities or events which disturb ecosystem state and function. Examples are: landscape disturbance in agriculture, mining, forestry, urbanization, and natural disasters. An understanding of these links can provide guidance for management interventions and policy options that promote human health. An ecosystem approach to management must be adaptive because of irreducible uncertainty in ecosystem function. A promoção da saúde humana deve estar embutida na busca maior pela saúde do ecossistema. As intervenções estarão prejudicadas se os determinantes ecossistêmicos da saúde não forem levados em conta. Em caso extremo, se os ecossistemas perderem a capacidade de se renovarem, a sociedade ficará privada de serviços essenciais à sustentação da vida. As características essenciais da saúde ecossistêmica são a capacidade de manter a integridade e a de atingir metas humanas razoáveis e sustentáveis. Uma abordagem ecossistêmica para a pesquisa e gestão deve ser transdisciplinar e assegurar a participação dos diferentes atores. Tais características fornecem um meio à ciência para lidar melhor com a complexidade dos ecossistemas, bem como aos políticos e gestores no sentido de definir e atingir metas societais razoáveis. A abordagem ecossistêmica é capaz de determinar elos entre a saúde humana e as atividades ou os eventos que perturbam o estado e a função ecossistêmicos. A compreensão desses elos pode orientar as intervenções e as opções políticas que promovem a saúde humana. Uma perspectiva ecossistêmica na gestão deve ser adaptável, devido à incerteza irredutível da função ecossistêmica.